Students’ Voices of Teachers’ Online Written Feedback - Lailatus Sa'adah; Rosi Anjarwati; Mohammad Romadhoni; Eva Nikmatul Rabbianty (IAIN MADURA, 2023)
Feedback should be beneficial to learners; it should provide information about their performance of a task or activity. This study aims to explore students' concerns and expectations toward teachers' online written feedback through photovoice. Participants involved fifteen students of a writing course. To obtain the data, a photovoice was used following Wang et al.'s SHOWeD protocols based on the theme